EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION BERPENDEKATAN ETNOSAINS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI STOIKIOMETRI - Tin Rosidah; Fitria Fatichatul Hidayah; Andari Puji Astuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to determine the effect of problem based instruction learning model with ethnicscience approach to students' learning achievement on stoichiometric material. This study uses a quasi-experimental method with the times series design. Determination of the sample using purposive sampling technique. Data collection techniques were carried out by measuring question instruments, observations, and open interviews, as well as student response questionnaires. The pretest and posttest implementation in this study was conducted four times. The results of the study obtained the value of N-Gain at each pretest and posttest which was carried out four times. The first N-gain is 0.788, the second N-Gain is 0.785, the third N-Gain is 0.774, and the fourth NGainis 0.753. The fourth value of N-Gain is in the high category. To test thehypothesis, non-parametric t-test is used because the data obtained is not normal. Based on the t test that has been done, it is obtained data of sig 2 tailed value of 0.00. It can be concluded that there is a significant effect on the use of problem based instruction learning models with ethnains approach to student achievement on stoichiometric material. This model is also effective in improving students' learning achievement on stoichiometric material as seen from the high number of effect sizes, namely 98%, 98%, 96%, and 95%. Individual and classical completeness tests obtain results of 79.55 and 85.64% respectively and can be categorized completely. Keywords: Problem Based Instruction, ethnoscience, learning achievement, stoichiometry